SISTEM INFORMASI PENGOLAHAN DATA TRANSAKSI PENJUALAN PADA TOKO PERTANIAN ARDIA TANI MAKMUR - Sri Mulyati (JURNAL AKADEMIKA)
Farms store Ardia Tani Makmur as drug - store fertilizers and other agricultural ty that sells various types of fertilizers and medicines . Ardia Tani Makmur Toko Agriculture is still using the conventional system in preparing reports sales transaction , so it is still frequent errors in preparing reports . The purpose of the research is the creation of an information system to facilitate reporting of sales transactions . The method used is literature , observation , interviews , analysis, design , manufacture program . With this system is expect ed to help process transactions so users can process data more quickly and can generate precise information .